Parametric Study of a Ball-Screw Energy Harvester Shock Absorber - Djellal Hajar; Morrone Biagio; Costanzo Luigi; Vitelli Massimo; Saad Aouatif (E3S Web of Conferences)
This paper investigates a ball-screw energy harvester shock absorber (BS-EHSA) equipped with a DC motor/generator and driven by an external sinusoidal force. A comprehensive parametric study examines the effect on the power delivered to the load of varying the sprung mass, external electrical resistance, and spring constant. A simulation study is also performed to demonstrate how the resonance frequency of the system impacts energy recovery. Numerical simulations are carried out in the MATLAB environment, providing insights into optimizing system parameters for maximum power efficiency.